A controlled study of Gd-EOB-DTPA-enhanced MRI compared with enhanced CT in assessing lesion status after TACE for hepatocellular carcinoma - Cheng, Qichao; Peng, Xuewen; Zhou, Zhanyu; Wang, Bowen; Fan, Jinlei; Zuo, Liping; Lv, Weiwei; Yu, Dexin (Frontiers in Medicine, 2025)
ObjectiveThis study aims to evaluate the diagnostic capability of Gd-EOB-DTPA-enhanced MRI in assessing lesion status following transcatheter arterial chemoembolization (TACE) for hepatocellular carcinoma (HCC), in comparison to contrast-enhanced CT (CECT).MethodsA total of 56 patients with HCC who underwent Gd-EOB-DTPA-enhanced MRI and CECT scans post-TACE were initially enrolled. The ability of both imaging modalities to differentiate between surviving, new, or necrotic lesions was assessed, using digital subtraction angiography (DSA) or interventional diagnostic results as the reference standard. Detection rates were compared using the chi-square test, while sensitivity, specificity, and accuracy were analyzed with McNemar’s test.ResultsAfter applying inclusion and exclusion criteria, 48 patients were eventually included in the analysis. The reference standard identified 14 cases of surviving lesions, 19 of new lesions, and 15 of necrotic lesions. Gd-EOB-DTPA-enhanced MRI demonstrated a sensitivity of 93.9% (31/33), specificity of 100% (15/15), and a Youden index of 0.939, whereas CECT exhibited a sensitivity of 51.5% (17/33), specificity of 60.0% (9/15), and a Youden index of 0.115.ConclusionThe findings indicate that Gd-EOB-DTPA-enhanced MRI possesses superior diagnostic value for evaluating lesion status in HCC post-TACE compared to CECT, as evidenced by significant differences in sensitivity and specificity (p < 0.05).